Design Prospects of Parallel U-shaped Multi-Resonator for Fabric-based Chipless RFID Tags - Khan, Sanaullah; Hossain, A K M Zakir; Kayser Azam, S. M.; Othman, Mohamadariff; Hassim, Nurulhalim (2023)
This paper introduces a new 10-bit planar parallel U-shaped multi-resonator (PUMR) that is designed specifically for retransmission-based chipless radio frequency identification (CRFID) applications, with the aim of enabling its integration into fabric-based CRFID systems. The PUMR functions within the ultra-wide band (UWB) frequency spectrum. Simulation of the PUMR was carried out on two distinct PCB types, namely Rogers 3003 and Rogers 5880, as well as five different fabric-based substrates: pile, denim, silk, felt, and fleece. The results reveal a good spectral density (bits/GHz) of up to 4.7 bits/GHz was achieved using the Rogers 5880 substrate within a bandwidth of 2.13 GHz. Also, the design displays a good spatial density of ~ 11 bit/cm2. The PUMR design exhibits a coding capacity of up to 10 bits. The effectiveness of the proposed design was demonstrated by employing various extracted bit streams, such as 1111111111, 0000000000, 0101010101, 1010101010, and 0101000101. Additionally, a bending analysis was conducted to assess the suitability of the design on fabric. These findings showcase the efficiency of the proposed PUMR design and provide an incentive for CRFID designers to develop compact, high-capacity tags in UWB range.